2009
DOI: 10.1177/097324700900500102
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Innovation

Abstract: The paper considers the importance of interaction of entrepreneurship and innovation. Tracing the definition of entrepreneurship, the paper puts forward some of the important characteristics of entrepreneur-ship and how it has evolved over a period of time and what exactly it is today. Discussing the types of entrepreneurship, the paper presents the characteristic traits of entrepreneurs and how to profile them. The ability to take risks and indulge in creative destruction and innovation are shown as distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
0
14
0
9
Order By: Relevance
“…Este crescimento organizacional apontado por Norrman e Bager-Sjögren (2010) pode ser explicado pela forma como as inovações são alcançadas. Veeraraghavan (2009) sugere uma combinação de muitos fatores como fundamentais na tarefa de empreender, incluindo o histórico familiar, habilidade para assumir riscos e forma de colocar novas ideias para serem realizadas. O empreendedor precisa de características distintas: jeito para tratar riscos e conhecimento sobre a destruição criativa (Schumpeter,1934).…”
Section: Inovaçãounclassified
“…Este crescimento organizacional apontado por Norrman e Bager-Sjögren (2010) pode ser explicado pela forma como as inovações são alcançadas. Veeraraghavan (2009) sugere uma combinação de muitos fatores como fundamentais na tarefa de empreender, incluindo o histórico familiar, habilidade para assumir riscos e forma de colocar novas ideias para serem realizadas. O empreendedor precisa de características distintas: jeito para tratar riscos e conhecimento sobre a destruição criativa (Schumpeter,1934).…”
Section: Inovaçãounclassified
“…El concepto de emprendimiento surge inicialmente de la unión de los vocablos francés entreprendre, y alemán unternehmen, que significan emprender (Veeraraghavan, 2009). Este vocablo emprendedor se asume como de origen francés y se refiere a quien asume riesgos, es decir, aquel que persigue beneficios y trabaja en equipo o individualmente, innovando, creando oportunidades de negocio (Hisrich, 1990;Bruneau & Machado, 2006).…”
Section: Fundamentación Teórica: Emprendimiento E Intraemprendimientounclassified
“…Then entrepreneurship helps to generate new idea for economy, create culture of independence, risk taking and confidence. As a result, the combination of the factors of innovation and entrepreneurship leads to businesses achievement [13].…”
Section: The Important Of Entrepreneurship and Innovationmentioning
confidence: 99%
“…While, innovation at all segments and organization levels is imperative for organizations [10] as it involves a complex process with multiplex links between new technology and science as well as capability producers and buyers [11] and, as a result, the businesses can build up the technological capabilities that will allow them to innovate better than other firms [12]. Veeraraghavan [13] concluded that a combination of the Innovation and entrepreneurship factors would lead to successful businesses.…”
Section: Introductionmentioning
confidence: 99%